2018
DOI: 10.1007/s00737-018-0880-8
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal depressive symptoms in women with and without antenatal depressive symptoms: results from a prospective cohort study

Abstract: Evidence exists that the risk factors for depression in the antenatal and postnatal period may differ, but only a handful of studies looked at depression longitudinally. The aims of this study were (1) to estimate the prevalence of postnatal depressive symptoms in Kuwait where data about postnatal depression are scarce and identify its determinants and (2) to compare these risk factors between women who had experienced antenatal depressive symptoms and those that did not. Data collected in the TRansgenerationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 49 publications
3
24
0
Order By: Relevance
“…Similarly, in relation to the S-BSS-R SE sub-scale women experiencing an unassisted delivery scored significantly higher compared to those receiving an intervention, thus, and again consistent with other studies (Fleming et al, 2016;Hollins Martin and Martin, 2014;Jefford et al, 2018), indicating that assisted delivery is associated with less satisfaction and more stress. Given the relationship of stress as a fundamental component to distinct perinatal mental health presentations, ranging from postpartum posttraumatic stress disorder (Ali, 2018;Dikmen-Yildiz et al, 2017;Shlomi Polachek et al, 2016), tokophobia (Goutaudier et al, 2018;Striebich et al, 2018) and postnatal depression (Dennis et al, 2018;Pampaka et al, 2018), this finding yields valuable data regarding the potential implications of delivery type on psychological well-being and the development of psychiatric disturbance. Focusing upon the S-BSS-R QC sub-scale we noted that women who had an assisted delivery were significantly less satisfied in terms of quality of care received compared to those who had an unassisted delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in relation to the S-BSS-R SE sub-scale women experiencing an unassisted delivery scored significantly higher compared to those receiving an intervention, thus, and again consistent with other studies (Fleming et al, 2016;Hollins Martin and Martin, 2014;Jefford et al, 2018), indicating that assisted delivery is associated with less satisfaction and more stress. Given the relationship of stress as a fundamental component to distinct perinatal mental health presentations, ranging from postpartum posttraumatic stress disorder (Ali, 2018;Dikmen-Yildiz et al, 2017;Shlomi Polachek et al, 2016), tokophobia (Goutaudier et al, 2018;Striebich et al, 2018) and postnatal depression (Dennis et al, 2018;Pampaka et al, 2018), this finding yields valuable data regarding the potential implications of delivery type on psychological well-being and the development of psychiatric disturbance. Focusing upon the S-BSS-R QC sub-scale we noted that women who had an assisted delivery were significantly less satisfied in terms of quality of care received compared to those who had an unassisted delivery.…”
Section: Discussionmentioning
confidence: 99%
“…The 81 cohort studies were published between 1990 in Saudi Arabia [40,79] and 2019 in Kuwait [41], Qatar [42,60,61], and Saudi Arabia [80]. The size of the cohorts ranged from 23 pregnant women with a known diagnosis of idiopathic thrombocytopenic in Saudi Arabia [62] to 158,006 delivering mothers in Kuwait [81].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Thirty-four cohort studies (42.0%) were identified as a prospective design (19 in [81], and three in the UAE). Fiftytwo (64.2%) cohort studies enrolled pregnant mothers at varying stages of their pregnancy with different characteristics such as diabetic and non-diabetic mothers [26,67], obesity [42,47,54], singleton [41,48,99] or triplet pregnancies [91], teenage women [112], multipara women [82,86,98], and women with systemic lupus erythematosus (SLE) [27]. Eight studies (9.9%) enrolled pregnant mothers at varying stages after delivery [24,49,58,59,81,84,88,99].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Antenatal depression which can occur in any time during pregnancy, has been considered as a major public health problem. The consequences of antenatal depression may be severe and far-reaching, negatively affecting the mother and infant [1,2], including the increased risk of perinatal complications, adverse perinatal outcomes [3], and adverse effects on the development of infant cognition, behavior, emotion and intellectual [4].Evidence has shown that 50% postpartum depression begins at antenatal period [5], and antenatal depression is the most effective predictive factor for postpartum depression [6]. However, due to some physiological symptoms of pregnancy are overlapped with the antenatal depressive symptoms, it is difficult to well recognize the antenatal depressive symptoms [7].…”
Section: Introductionmentioning
confidence: 99%